Development of digital pop-up book media to improve learning outcomes about Denok Semarang dance - Fairuz Intan Amalia; Atip Nurharini (Research and Development in Education (RaDEn), 2025)
This research is motivated by the fact that many teachers have not been optimal in using innovative digital technology-based learning media. This causes low learning outcomes for grade IV students in the Semarang Denok dance material. This study aims to develop learning media designs, test the feasibility, and test the effectiveness of digital pop-up book media in fourth grade at Ngaliyan 01 Elementary School, Semarang. This type of research is R&D (Research and Development) research with the ADDIE model using five stages: Analyze, Design, Develop, Implement, and Evaluate. The techniques used in data collection are tests and non-tests (material expert and media expert validation sheets, teacher response questionnaire sheets, student responses, interviews, and documentation. Validation from material experts). The results of the study showed that (1) digital media was developed using the Canva, Power-point, and Cap-cut applications with book cover components, book pages containing material and videos, and book covers; (2) the feasibility of media expert products was 95%, material experts 97.5%, student responses 87.5% and teacher responses 95% with very feasible criteria; (3) effectiveness is seen from the increase in learning outcomes of 19.4949 and Sig. (2-tailed) of 0.000 which shows that there is a significant difference in students before and after using digital media. The N-Gain test obtained was 0.6369 which shows moderate criteria. The conclusion of this study states that the digital pop-up book media has been successfully developed, is feasible, and is effective in learning dance arts on the Denok Semarang Dance material.